Thermal design and optimization of lithium ion batteries for unmanned aerial vehicles. Issue 1 (29th April 2019) - Ma, Yanjun; Chiang, Sum Wai; Chu, Xiaodong; Li, Jia; Gan, Lin; Xu, Chengjun; Yao, Youwei; He, Yanbing; Li, Baohua; Kang, Feiyu; Du, Hongda
Abstract: In this article, a novel lithium ion batteries thermal design to manage ultrahigh thermal shock of a commercial small four‐rotor electric unmanned aerial vehicle (UAV) is developed and optimized. The cooling relies on internal heat pipe and convective cooling of UAV body, so that the heat generated by the battery can reach exterior cooling through a dedicated thermal path. The thermal management system is passive and requires no additional energy consumption. Finite element simulation is established to model the system and advanced thermal materials, and the system is optimized by response surface method in a dual objectives approach: minimizing maximum battery temperature and weight of the UAV. Simulation results show that the new passive cooling system can keep the temperature of the lithium ion battery within a reasonable range. The effects of convective heat transfer coefficient, discharge rate, and fuselage thermal conductivity were studied. After optimizing the system, the highest temperature of battery discharging at 3C rate can be kept no more than 36°C in the cost of 32.18 g weight increment.